Rubisco and Rubisco Activase Play an Important Role in the Biochemical Limitations of Photosynthesis in Rice, Wheat, and Maize under High Temperature and Water Deficit - Perdomo, Juan A.; Capó-Bauçà, Sebastià; Carmo-Silva, Elizabete; Galmés, Jeroni (Frontiers in Plant Science, 2017)
To understand the effect of heat and drought on three major cereal crops, the physiological and biochemical (i.e. metabolic) factors affecting photosynthesis were examined in rice, wheat and maize plants grown under long-term water deficit (WD), high temperature (HT) and the combination of both stresses (HT-WD). Diffusional limitations to photosynthesis prevailed under WD for the C3 species, rice and wheat. Conversely, biochemical limitations prevailed under WD for the C4 species, maize, under HT for all three species, and under HT-WD in rice and maize. These biochemical limitations to photosynthesis were associated with Rubisco activity that was highly impaired at HT and under HT-WD in the three species. Decreases in Rubisco activation were unrelated to the amount of Rubisco and Rubisco activase (Rca), but were probably caused by inhibition of Rca activity, as suggested by the mutual decrease and positive correlation between Rubisco activation state and the rate of electron transport. Decreased Rubisco activation at HT was associated with biochemical limitation of net CO2 assimilation rate (AN). Overall, the results highlight the importance of Rubisco as a target for improving the photosynthetic performance of these C3 (wheat and rice) and C4 (maize) cereal crops under increasingly variable and warmer climates.